2022
DOI: 10.1186/s12876-022-02497-2
|View full text |Cite
|
Sign up to set email alerts
|

Bowel preparation using 2-L split-dose polyethylene glycol regimen plus lubiprostone versus 4-L split-dose polyethylene glycol regimen: a randomized controlled trial

Abstract: Background Colonoscopy is a standard procedure for evaluating colon diseases and screening for colorectal cancer, and bowel cleanliness prior to colonoscopy is key. The aim of this study was to compare the bowel cleansing efficacy of low-volume (2 L) split-dose polyethylene glycol (PEG) plus single-dose (24 µg) lubiprostone (LB) and high-volume (4 L) split-dose PEG. Methods Patients scheduled to undergo outpatient colonoscopy between December 2019 and June 2021 at Rajav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…The BBPS is a valid and reliable instrument for rating the quality of bowel preparation during colonoscopy ( 15 ). One study showed that the PEG combined with lubiprostone (LB, 24 µg) could enhance the rate of adequate bowel preparation, rather than affecting the mean total and segment-specific BBPS scores ( 20 ). Conversely, another study showed that the PEG combined with mosapride could elevate the total BBPS score with better bowel preparation efficacy and lower adverse events, as opposed to affecting the rate of adequate bowel preparation (BBPS ≥6) ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The BBPS is a valid and reliable instrument for rating the quality of bowel preparation during colonoscopy ( 15 ). One study showed that the PEG combined with lubiprostone (LB, 24 µg) could enhance the rate of adequate bowel preparation, rather than affecting the mean total and segment-specific BBPS scores ( 20 ). Conversely, another study showed that the PEG combined with mosapride could elevate the total BBPS score with better bowel preparation efficacy and lower adverse events, as opposed to affecting the rate of adequate bowel preparation (BBPS ≥6) ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The endoscopist used the Boston Bowel Preparation Scale (BBPS) [ 15 ] to score the cleanliness of the three colonic segments of the patient’s right colon (including ileocecal and ascending colon), transverse colon (including hepatic flexure and splenic flexure), and left colon (including descending colon, sigmoid colon, and rectum). The scoring criteria were as follows: 0, a solid stool could not be removed from the intestinal cavity and the entire intestinal mucosa was not visible; 1, the intestinal cavity was still filled with stool or dark liquid, and part of the intestinal mucosa was visible; 2, a small amount of stool or dark liquid remained in the intestinal cavity and the intestinal mucosa was visible; 3, the intestinal cavity did not contain any stool or dark liquid and the entire intestinal mucosa was visible.…”
Section: Methodsmentioning
confidence: 99%